2019
DOI: 10.5114/pg.2019.85895
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C infection: how much are physicians aware of?

Abstract: AimThe purpose of our study is to measure the awareness of hepatitis C among physicians employed in Istanbul, and investigate the relationship between awareness and the specialization field, age and presence of chronic hepatitis/positive family history.Material and methodsLevel of awareness of 125 family physicians and 76 internal medicine physicians, employed within Istanbul Province, on hepatitis C infection were evaluated using standard questionnaire. Relationship between their awareness and age, specializa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the survey study of 125 family physicians and 76 internal medicine physicians by Kayar et al it was found that the awareness of physicians about transmission routes and the patient groups needing to be screened for anti-HCV was low [17]. Another study revealed that the success of the disease treatment is asso-ciated with the knowledge of primary care physicians on the diagnosis and screening of HCV [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the survey study of 125 family physicians and 76 internal medicine physicians by Kayar et al it was found that the awareness of physicians about transmission routes and the patient groups needing to be screened for anti-HCV was low [17]. Another study revealed that the success of the disease treatment is asso-ciated with the knowledge of primary care physicians on the diagnosis and screening of HCV [18].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness about HCV diagnosis and treatment among physicians has been evaluated in some studies. Kayar et al determined that the physicians were insufficient in answering the questions on HCV screening [19]. A survey study reported that 44% of the Chinese nonspecialist physicians thought that anti-HCV positive patients do not need the further examination [20].…”
Section: Discussionmentioning
confidence: 99%